2021
DOI: 10.3390/pr9071204
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Single and Combined Use of Ergothioneine, Ferulic Acid, and Glutathione as Antioxidants for the Prevention of Ultraviolet B Radiation-Induced Photoaging Damage in Human Skin Fibroblasts

Abstract: Ultraviolet B (UVB) irradiation can cause human skin damage or skin aging and wrinkle formation through photochemical reactions. Antioxidative substances may ameliorate UV damage. In this study, the anti-photoaging activity of three antioxidants—ergothioneine, ferulic acid, and glutathione—was investigated after UVB irradiation of Hs68 human skin fibroblast cells. The cells treated with these three antioxidants appeared similar to unirradiated control cells. UVB irradiation decreased cell viability by 26% comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Meanwhile, EGT inhibits the production of these ROS (28)(29)(30)(31), reduces UV-induced oxidative damage to cell components, and decreases apoptotic responses in keratinocytes (15). Additionally, The effects of hiratake on skin moisture content among participants with a low baseline EGT concentration (< 3. in cultured UV-irradiated skin fibroblasts, EGT alleviates the decrease in collagen production (17,32); increase in expression of matrix metalloproteinase-1 (17,32), a major collagenolytic enzyme; and increase in gene expression of cellular communication network factor 1 (17), which is associated with diminished skin barrier function and reduced moisture (33). Therefore, EGT may have the potential to mitigate UV-induced oxidative stress and disruption of extracellular matrix homeostasis in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, EGT inhibits the production of these ROS (28)(29)(30)(31), reduces UV-induced oxidative damage to cell components, and decreases apoptotic responses in keratinocytes (15). Additionally, The effects of hiratake on skin moisture content among participants with a low baseline EGT concentration (< 3. in cultured UV-irradiated skin fibroblasts, EGT alleviates the decrease in collagen production (17,32); increase in expression of matrix metalloproteinase-1 (17,32), a major collagenolytic enzyme; and increase in gene expression of cellular communication network factor 1 (17), which is associated with diminished skin barrier function and reduced moisture (33). Therefore, EGT may have the potential to mitigate UV-induced oxidative stress and disruption of extracellular matrix homeostasis in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…The specific effect of EGT on the antioxidant network remains unclear; however, it has been shown that EGT can improve the stability of other antioxidant substances and even play a synergistic role in the body. Gregory et al [ 66 ] confirmed the excellent antioxidant properties of EGT using the three antioxidants (EGT, ferulic acid, and GSH) separately and in combination. EGT had stronger antioxidant properties when 50 μM EGT was combined with 100 μM ferulic acid, which prevented oxidative damage and photoaging of skin cells.…”
Section: The Biological Effect Of Ergothioneinementioning
confidence: 99%
“…As the best known dietary sources of EGT, mushrooms and cyanobacteria have good nutritional value, medicinal value, and cosmetic value [19], mainly because their components have good antioxidant and anti-inflammatory effects [20][21][22], antioxidant capacity of EGT accounts for about 25% of the total antioxidant capacity of fungi extracts [23]. For the excellent free radical scavenging ability, excellent light, heat, and acid-base stability, it had shown good antioxidation, whitening [4,24], and antiphotoaging functions when EGT was applied to cosmetics [25,26]. Due to the excellent effect of EGT, it has become a gimmick for highend cosmetics publicity.…”
Section: Introductionmentioning
confidence: 99%